(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The study examined the discursive strategies in media representation of the Sit-at-Home order dished out in the south east region of Nigeria. Taiwo and Igwebuike (2015); Igwebuike (2018); Ajiboye and Abioye (2019); and Chiluwa (2011) are some of the studies carried out on media representation of socio-political issues in Nigeria. The extant studies focus on Media representation of the Bakassi-Cameroun conflict, Niger-Delta Crisis and online discourse of Biafra agitations. The studies on Biafra agitations take little or no cognizance of the (Monday) Sit-at-home exercise, therefore the present study fills the existing gap in knowledge. Data were collected from websites of Premium Times, the Guardian, BusinessDay, National Daily Newspaper and Radio Biafra’s Facebook page. Textual analysis was done using Wodak’s Discourse Historical Approach. Findings reveal that the media employ discursive strategies of nomination, predication, perspectivization/framing and intensifying/mitigation to represent the sit at home exercise as a threat to national development in the south east region of Nigeria and the cause of loss of lives and properties. But members of the Indigenous people of Biafra (IPOB) and actors insist that the Sit-at-home exercise is a tool of civil disobedience and a form of protest. The study concludes that the media employs self-glorification and other derogation in reporting the Sit at home orders in the southeast. This has shaped the way people view the orders and may have contributed to the continued detention of the IPOB leader.